Immune Checkpoints: Novel Therapeutic Targets to Attenuate Sepsis-Induced Immunosuppression - McBride, Margaret A.; Patil, Tazeen K.; Bohannon, Julia K.; Hernandez, Antonio; Sherwood, Edward R.; Patil, Naeem K. (Frontiers in Immunology, 2021)
Sepsis is a leading cause of death in intensive care units and sepsis survivors suffer prolonged immunosuppression and a high incidence of recurrent infections. No definitive therapeutics currently exist to treat sepsis and physicians must rely on supportive care including antibiotics, fluids and vasopressors. With the rising incidence of antibiotic resistance microbes, it’s becoming increasingly critical to discover novel therapeutics. Sepsis-induced leukocyte dysfunction and immunosuppression is recognized as an important contributor towards increased morbidity and mortality. Pre-clinical and clinical studies show that specific cell surface inhibitory immune checkpoint receptors and ligands including PD-1, PD-L1, CTLA4, BTLA, TIM3, OX40 and 2B4 play important roles in the pathophysiology of sepsis by mediating a fine balance between host immune competency and immunosuppression. Pre-clinical studies targeting the inhibitory effects of these immune checkpoints have demonstrated reversal of leukocyte dysfunction and improved host resistance of infection. Measurement of immune checkpoint expression on peripheral blood leukocytes could also serve as a means of stratifying patients to direct individualized therapy. This review will focus on the advances in our understanding of the role of immune checkpoints in the host response to infections and the potential clinical application of therapeutics targeting the inhibitory immune checkpoint pathways for the management of septic patients.